Pengembangan Modul Evolusi Berbasis Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar Kognitif Mahasiswa di Jurusan Biologi Institut Agama Islam Negeri Kerinci - Nosi Qadariah (Symbiotic: Journal of Biological Education and Science, 2022)
The Indonesian National Qualifications Framework is a reference for the implementation of lectures at the State Islamic Institute Kerinci. The Indonesian National Qualifications Framework requires students to have good cognitive learning outcomes. One material that is difficult for students to understand is evolution. The cause of the difficulty of evolutionary material is the unavailability of learning resources that provide examples according to students' real lives. The solution to overcome the low cognitive learning outcomes of students on evolutionary material is the development of an evolutionary module based on Problem Based Learning (PBL). This study aims to produce an an evolutionary module based on Problem Based Learning that is valid, practical, effective. This research is a development research using the ADDIE model which consists of the analysis, design, development, implementation, and evaluation stages. The resulting data are qualitative and quantitative data. Module is very valid, very practical, effective for improving cognitive learning outcomes. The validity value of media experts is 89.8%, material experts are 90.8%, and field practitioners are 91.2%, the practicality value is 91.8%. Evolution module based on PBL is effective for improving cognitive learning outcomes with an F value of 7.489 with p-value = 0.008 < (α = 0.05).